PEMANFAATAN CERITA RAKYAT PAPUA SEBAGAI MEDIA PENGEMBANGAN KARAKTER ANAK-ANAK DI KAMPUNG HARAPAN, KABUPATEN JAYAPURA - Lisye Iriana Zebua; Wigati Yektiningtyas; Rosye H.R. Tanjung; Hanna E. Samosir (JURNAL PENGABDIAN PAPUA, 2022)
Character education is now indeed a major issue of education, apart from being part of the process of forming the nation's children's morals, character education is also expected to be the main foundation in the success of Indonesia Gold 2025. Character education can be given early in early childhood through the media of fairy tales. The importance of fairy tales for early childhood is not only an activity to put children to sleep but can also improve the development of the child's right brain, psychology, emotional intelligence, noble character, and increase imagination in early childhood. Telling fairy tales to children is an important part of parenting. Besides being useful for psychological development, it also makes children feel loved and cared for by their parents. So that it does not cause moral degradation amid the rapid development of technology today. Through fairy tales as a medium for character education in early childhood, children will be able to learn about the world, life, themselves, and others. Keywords:  Character education, psychology, emotional intelligence, Jayapura